(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe burn characteristics and initial first-aid practices among pediatric burn patients treated at the Burn Department of Saint Paul General Hospital, Hanoi, from June to August 2025. Methods: A prospective descriptive cross-sectional study included 50 pediatric burn patients aged 0–15 years. Epidemiological characteristics, burn injuries, and first aid at the injury scene were summarized using frequencies and percentages. Results: Children aged 1–3 years accounted for 42%, and boys for 64%. Scalds accounted for 92%, and all recorded injuries occurred at home. Lower limbs were the most frequent site (28.9% of recorded sites). Total burn surface area was available for 48/50 children: 24/48 (50.0%) had <10% and 4/48 (8.3%) had ≥30% total body surface area burned. Deep burn area <5% (including 0%) accounted for 50.0%; no deaths were recorded. Water cooling was reported in 52%, while 38% received no first aid and 10% received inappropriate first aid. Conclusion: In this three-month, single-department series of 50 patients, burns clustered among young children, were predominantly scalds, and occurred at home. Household prevention and guidance on cooling burns with cool running water should be strengthened.